2019
DOI: 10.1093/jmt/thz009
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Home-Based Neurologic Music Therapy for Behavioral and Psychological Symptoms of Dementia: A Pilot Study

Abstract: Family caregivers often feel ill-equipped to handle bothersome behavioral and psychological symptoms of dementia, such as agitation, apathy, and sleep disturbances, leading to increased caregiver distress and nursing home placement for people with dementia. Therapies for such symptoms are currently limited and non-pharmacological options are preferred, given potential side effects of medications. Neurologic music therapy (NMT) could provide an additional treatment option for managing behavioral and psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…32 In a study where Holden et al administered neurological music therapy in home visits for six weeks to dementia patients, it was found that there was a decrease in the neuropsychiatric symptoms of the patients. 33 In a study where Parajuli et al applied individualized music therapy and cared for patients with dementia according to PLST, it was reported that although there was a decrease in the psychotropic, antipsychotic, and antidepressant drugs used by the patients for three months, the difference was not statistically significant. 34 In the study by Akpınar 12 In a study by Chrabaszcz, caregivers of dementia patients were trained according to the PLST model and it was found that there was a minimum decrease in the behavioural problems of the dementia patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 In a study where Holden et al administered neurological music therapy in home visits for six weeks to dementia patients, it was found that there was a decrease in the neuropsychiatric symptoms of the patients. 33 In a study where Parajuli et al applied individualized music therapy and cared for patients with dementia according to PLST, it was reported that although there was a decrease in the psychotropic, antipsychotic, and antidepressant drugs used by the patients for three months, the difference was not statistically significant. 34 In the study by Akpınar 12 In a study by Chrabaszcz, caregivers of dementia patients were trained according to the PLST model and it was found that there was a minimum decrease in the behavioural problems of the dementia patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, NMT has been used to aid the psychosocial symptoms of dementia. 44 Techniques such as Musical Sensory Orientation Therapy and Musical Attention Control Therapy use elements of musicality, such as rhythm and melody to both orient the participants in time and space and to improve attentive functions. Although not always successful, such studies have assessed the question as to how important knowing the music actually is and whether it is the elements of the music, and not just the emotional attachment that provides the response in participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although not always successful, such studies have assessed the question as to how important knowing the music actually is and whether it is the elements of the music, and not just the emotional attachment that provides the response in participants. 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el campo de la demencia, Fakhoury et al (2017) observan que las intervenciones musicoterapéuticas disminuyen fuertemente la ansiedad y tienen el potencial de mejorar la calidad de vida. Holden et al (2019) sostienen que, aplicada en el hogar, ayuda a reforzar un grado de independencia a estos pacientes y sus cuidadores, permitiendo una traducción directa de beneficios a su vida diaria. Lam et al (2020) encuentran que "podría mejorar la fluidez verbal y reducir la ansiedad, la depresión y la apatía en pacientes con demencia, aunque no parece haber beneficios comprobados en memoria, función diaria o calidad de vida en general.…”
Section: Introductionunclassified